ENCOURAGING STUDENT PROFESSIONALISM AND CAREER READINESS: A QUALITATIVE STUDY AT PRE-INTERNSHIP SEMINAR - Asri Essada Nurachmah; Syachriani Syam (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
The dynamics of national and international companies force employees to quickly adapt to fluctuating, uncertain, complex, and ambiguous situations. Unfortunately, this situation can only be understood if new graduates enter the workforce as young employees. To be better prepared before entering a company, universities can organize pre-internship seminars as a step to help students familiarize themselves with actual working conditions. This paper aims to explore how students prepare for their professional careers by listening to practitioners as a persona for knowledge transfer. Qualitative research is used to illustrate the objective results of knowledge transfer and to obtain participants' perspectives on the quality of the seminars. This study uses data through direct observation and interviews with student representatives using six dimensions of professional behavior and exploring communication tools that apply business communication theory. The findings indicate that the seminar activities successfully increase student self-confidence, increase student attention to forms of mental preparation, including self-confidence training, and are necessary as an annual institutional event.